DEVELOPMENT OF A BLUEPRINT FOR AN INFORMATION SYSTEM TO MONITORING THE LEARNING PROCESS POST-COVID-19 PANDEMIC - Yuniana Cahyaningrum (Social Sciences Journal, 2023)
The COVID-19 pandemic has had a significant impact on the education sector, forcing educational institutions to adapt distance learning models. Along with these changes, the need for efficient information systems to monitor and improve the learning process becomes increasingly urgent. This research aims to develop an information system blueprint that can provide a structured solution for monitoring the learning process after the COVID-19 pandemic. This blueprint is designed to provide a comprehensive overview of the key elements required in information systems development. The choice of research methodology focuses on analyzing the needs of stakeholders, including lecturers, students and academic administration, to ensure that this system can meet the expectations and needs of all relevant parties. Emphasis is also placed on the integration of the latest technology and the use of easily accessible digital platforms. In developing this blueprint, various aspects are explained, including the system architecture, modules to be implemented, and performance measurement methods. This system is designed to support collecting learning data, tracking student participation, and providing performance analysis that can be used as a basis for decision making to improve learning effectiveness. Through this approach, it is hoped that the development of a blueprint for an information system for monitoring the learning process after the COVID-19 pandemic can make a positive contribution to the learning experience, support the flexibility of learning models, and improve the overall quality of education. . The implementation of this blueprint is expected to provide a strong foundation for further information system development and support rapid adaptation to changing learning conditions in the future.